2021
DOI: 10.1177/17534666211049738
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 among patients with asthma and COPD: a report from the Swedish National Airway Register

Abstract: Background: Patients with obstructive lung diseases may be at risk of hospitalization and/or death due to COVID-19. Aim: To estimate the frequency of severe COVID-19, and COVID-19-related mortality in a well-defined large population of patients with asthma and chronic inflammatory lung disease (COPD). Further to assess the frequency of asthma and COPD as registered comorbidities at discharge from hospital, and in death certificates. Methods: At the start of the pandemic, the Swedish National Airway Register (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…SNAR is a national quality register launched in 2013 and includes data on patients from primary and secondary care with a physician diagnosis of asthma (children and adults) or chronic obstructive pulmonary disease (COPD). 6 , 13 , 14 In this study, we included adult patients (⩾18 years) with asthma diagnoses (International Classification of Diseases, version 10; ICD-10 J45) identified in extracted data from SNAR on 1 February 2020. Patients with COPD diagnosis (ICD-10 J44) were excluded from the study population.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SNAR is a national quality register launched in 2013 and includes data on patients from primary and secondary care with a physician diagnosis of asthma (children and adults) or chronic obstructive pulmonary disease (COPD). 6 , 13 , 14 In this study, we included adult patients (⩾18 years) with asthma diagnoses (International Classification of Diseases, version 10; ICD-10 J45) identified in extracted data from SNAR on 1 February 2020. Patients with COPD diagnosis (ICD-10 J44) were excluded from the study population.…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 Although a few studies have reported a prevalence of asthma up to 14% in hospitalized COVID-19 patients and asthma as risk factor for hospitalization, 3 , 4 there is growing evidence that asthma does not increase the risk of acquiring COVID-19. 5 In Sweden, the frequency of severe COVID-19 in asthma has been relatively low, 6 and several meta-analyses show that patients with asthma are not at risk of severe COVID-19-related outcomes such as hospitalization, intensive care, or mortality. 7 , 8 It has even been speculated that inhaled corticosteroid treatment might have a protective effect against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations